A quasi-optical microwave interferometer for the XuanLong-50 experiment. (11th August 2021) - Li, S.J.; Bai, R.H.; Tao, R.Y.; Li, N.; Lun, X.C.; Liu, L.C.; Liu, Y.; Liu, M.S.; Deng, B.H.
Abstract: A quasi-optical Mach-Zehnder microwave interferometer operating at 140 GHz has been developed for the ENN's spherical tokamak XuanLong-50 (EXL-50), for the purposes of line-integral electron density measurement and plasma density real-time feedback control input. The EXL-50 is designed for long pulse operation (over 5 s) and the electron density of phase I is estimated below 10 19 m -3 . Thus, the well-known microwave interferometer is suitable for the advantage of cost effectiveness and good stability. One of the major errors of the interferometer is vibration. To reduce it, the entire interferometer is supported by sand-filled stainless-steel columns of 0.3 m inner diameter and the vibration modes are calculated by finite elements analysis. Other sources of error, such as noise and thermal drift, are carefully handled. To reduce noise, the interferometer including cables and digitizers are carefully shielded and grounded. The phase error due to source frequency thermal drift, manifested due to uneven probe beam and reference beam path lengths, is observed in long term operation and explained by model calculation. A continuous 100 s test shows that it is reduced to about 0.04 °/s when the Gunn oscillators are temperature controlled by Peltier coolers with the industrial Proportional-Integral-Derivative control method to maintain the frequency stability. The system has been in routine operation since August 2019, with 10 16 m -2 line-integral density resolution. The technical details of the interferometer and experimental results are presented.